Nursing care for patients in palliative care (Research, Society and Development, 2021)
Palliative Care has competencies related to the physical, psychological, social and spiritual care of patients who face diseases that threaten their lives. This can and should be integrated early into the care for the control of the disease, and reduction of symptoms, thus generating an improvement in the quality of life. This research aims to describe the knowledge of the professional nurse in assistance to improve the quality of life, relieve pain and suffering of patients in palliative care. It is a narrative-type literature review with a qualitative approach, the search took place from September to December 2020 - it included free printed and online sources, such as manuals, protocols, articles and periodicals: Latin American Literature and of the Caribbean in Health Sciences (Lilacs), Bibliographic Specialized in the Brazilian Nursing Area (BDENF) and Medical Literature Analysisand Retrieval System Online (Medline). To operationalize the search, the resource was used: “PALLIATIVE CARE” [Subject descriptor] and “NURSING” [Subject descriptor] in the aforementioned databases. The nurse has a fundamental role in the promotion of PC, as in the acceptance of the diagnosis and help to live with the disease, providing comprehensive assistance to the user and everyone involved with the patient.